The Determination of “Basic Security Interests” in the WTO Security Exception Clause - Shuo Zhao (Studies in Law and Justice, 2023)
The WTO security exception clause is the product of balancing national security interests and economic and trade development. Because the terms of “basic security interests” are vague, there are some problems in the actual determination. By analyzing the problems in application, this paper concludes that the methodological path for determining basic security interests is subject to objective conditions and the principle of good faith, while taking into account the development of non-traditional security interests, under the prerequisite of safeguarding the right of members to self-determination. In today’s ever-changing political and economic situation, the game between development and security will be the background for a long time. How to promote members to reach a consensus on basic security interests within the WTO system is a new topic and challenge.